Pendampingan Pengembangan Pengetahuan Kebudayaan Gastronomi China untuk Guru dan Murid SMK Negeri 1 Gedangan Kabupaten Malang - Widyaningsih, Galih Edy Nur; Wulan, Diah Ayu; Octavia, Nurila Shanti (Jurnal Gramaswara: Jurnal Pengabdian kepada Masyarakat, 2024)
The community service activity of the Chinese Literature Study Program in 2023 was carried out at SMK Negeri 1 Gedangan. This vocational school was established in 2010 and offers the following vocational programs: Light Vehicle Technology, Multimedia, Catering Services, and Boutique Fashion. Among these programs, the study program conducted its community service activity in the Catering Services program. The community service was carried out in the form of mentoring or teaching Chinese Gastronomy (Cuisine) culture to teachers and third-year vocational high school students, totaling 30 students. This community service was conducted in several stages: planning, implementation, and evaluation. The outcomes of this community service program are: 1) Teachers at SMK Negeri 1 Gedangan have knowledge and understanding of the history and development of Chinese culinary culture; 2) Teachers at SMK Negeri 1 Gedangan have knowledge and understanding of Chinese culinary culture in Indonesia; 3) Teachers at SMK Negeri 1 Gedangan are aware of the differences between authentic Chinese culinary culture and Chinese culinary culture that has undergone cultural acculturation in Indonesia. 4) Teachers at SMK Negeri 1 Gedangan can practice cooking Chinese gastronomy. Keywords: gastronomy; vocational school; culinary arts/food service